Is the "Warm-up effect" in angina mediated by improved myocardial perfusion? - Kelion, A; Gardner, M; Hayton, S; Ormerod, O; Banning, A (2000)
Introduction. Considerable doubt remains about whether the "warm-up" effect in angina represents ischaemic preconditioning (IPC), or is simply due to improved myocardial perfusion via acute recruitment of collaterals. We investigated the latter possibility using quantitative tetrofosmin SPECT. Methods. 11 patients (age 63±8 years, 8 male) with coronary disease and preserved left ventricular function underwent symptom-limited treadmill exercise off antianginal medication. On three separate days at weekly intervals, 99mTc-tetrofosmin 400-450MBq was injected at rest, during a single exercise test (Ex1), and during the second of two exercise tests separated by 30 minutes (Ex2a and Ex2b). Exercise injections were given at equivalent heart rates. SPECT acquisitions were obtained 1-2 hours after each tetrofosmin injection. Quantitative analysis was performed by comparing polar plots derived from radial slices with a normal database. The "hypoperfusion index" was the product of perfusion defect extent and mean severity. Results. Haemodynamic and ECG indices were comparable between Ex1 and Ex2a. Compared with Ex2a, 1mm ST depression occurred later and at a higher heart rate during Ex2b. The reversible component of the hypoperfusion index was equivalent for Ex1 compared with Ex2b. Ex1 Ex2a Ex2b 1 mm time (min) 3.5±1.8 3.3±2.1 4.6±2.1* 1 mm HR (bpm) 130±15 128±16 139+20* Peak time (min) 6.8±1.8 7.0±1.7 7.3±1.2 Peak HR (bpm) 146±16 148±18 151±21 Data expressed as mean±SD * P<0.01 versus Ex2a Conclusion. The warm-up effect is not associated with a detectable improvement in myocardial perfusion using quantitative tetrofosmin SPECT. This supports IPC as the underlying cause. (Graph Presented).